Manajemen Waktu, Efikasi-Diri Dan Prokrastinasi - Ika Sandra, Kusnul (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract.The purpose of this study was to determine wheather there is a correlation  between time management (as variabel X1) and self efficacy (as variabel X2) with procrastination(as variabel Y),it has preseption if teacher’s procrastination can be reduce with good time management and high self efficacy. The populatiaon of  this study was teachers in senior high school and the same lavels who teach in Surabaya and Sidoarjo. Sampling technique used was propability sampling which is call purposive random sampling. The population and the sample are the same n = 110 and significance level of 21.3%. Data analysis used regression analysis using SPSS 18 for windows. The result tasks simultan got R = 0,461  F = 14,45, p = 0,000 (p < 0,01). It means that there are significant effect between time management and self efficacy with procrastination. The results of this study have shown significant effect, in which the time management and self efficacy affects procrastination althought the impact is very small because the coefficient of determination (R = 0,213) indicates that the relative contribution given by time management and seld efficacy to procrastination are only 21,3 % . Therefore there are 78.7 % of other factors that may determine the emergence of procrastination in teacher’s senior high schools.Key word: time management, self efficacy and procrastination